Group-based financial institutions for the rural poor in Bangladesh: an institutional- and household-level analysis - Zeller, Manfred; Sharma, Manohar; Ahmed, Akhter; Rashid, Shahidur (International Food Policy Research Institute, 2001)
Table of Contents: Tables, Figures, Foreword, Acknowledgments, and Summary; 1. Introduction; 2. Determinants of the Placement and Outreach of Group-Based Financial Institutions:A County-Level Analysis; 5. Analysis of the Household-Level Impact of Group-Based Credit Institutions in Bangladesh; 6. Conclusions and Implications for Policy; Appendix A: Survey Modules, Sampling Frame, and Location of Survey Sites; Appendix B: Adult Equivalent Consumption Units Differentiated by Age and Gender; References" 3. Group-Based Financial Institutions:Structure, Conduct, and Performance; 4. Household Participation in Financial Markets